School Libraries and Indexing in Brazil and Portugal - Terra, Ana Lucia; Lopes Fujita, Mariangela Spotti [UNESP]; Agustin Lacruz, Maria del Carmen (Ergon-verlag, 2016)
Research data on indexing policies in Brazilian and Portuguese school libraries are presented and discussed. Legal and organizational contexts regarding these types of libraries are briefly described. The collection of empirical data was obtained by means of an inquiry that resulted in 150 questionnaires from Brazil and 406 from Portugal. Based on these samples, a generic identification of school libraries was carried out in terms of teaching levels and institutional/geographical integration. The existence of a catalog in the libraries was also determined. The use of the two main kinds of indexing languages (classification systems and verbal indexing languages) were identified as well as the existence of manuals designed to guide indexing procedures. References are made to aspects related to the specificity and the number of terms/subjects selected for each document and the use of indexing norms by comparing both Brazilian and Portuguese realities.
Keywords: school libraries; indexing; use; Brazil; Portugal